A simple and flexible thermal illusion device and its experimental verification. Issue 8 (24th February 2015) - Chen, Tian Hang; Yang, Fan; Mei, Zhong Lei
<x xml:space="preserve">Abstract</x> A new kind of thermal illusion device is proposed, which requires one layer of homogeneous and isotropic thermal conducting materials. Unlike the transformation optics method, this illusion device is analytically designed by matching two distinct temperature profiles along a controlled boundary. We demonstrate that a good thermal conductor can be disguised as a poor one with the fabricated illusion device, and vice versa. And the simulation and experiment results agree well with each other. This kind of illusion device is very simple, flexible, and can be further improved for three dimensions. It also enjoys a variety of applications, such as military camouflage, heat flow manipulation, etc.